Unleashing EFL learning in the digital age: Online resources and student engagement - Herdi; Fauzan Fauzan; Ria Arista Asih; Ramanda Rizky (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2024)
When it comes to teaching and learning English, teachers and students face several challenges, particularly in terms of fatigue and uncertainty. As a result of this situation, English teachers must emphasize their concerns about using appropriate resources in English subjects in schools and colleges, such as using online learning resources to increase students' motivation to learn EFL. This present study is aimed at: (1) exploring the teaching materials, media, methods, strategies, teaching procedures/learning activities, and the assessments used in online learning resources to increase students’ motivation in EFL learning, and (2) investigating information in terms of students’ motivation documented with literature data serving as the primary source of information. While, the type of research was content analysis. The results show that through the use of relevant and engaging content, combined with technology-based tools and a student-centered approach, a dynamic learning environment is created. Therefore, the adaptability of assessments and learning activities to students' needs further supports their language development, fostering motivation and achievement in English language learning. Overall, a holistic approach that integrates these elements proves to be highly effective in promoting English proficiency through online resources.